Growth and productivity paradox. An estimation in the form of state-space, with unobservable components, for the Argentine agricultural sector, 1955-2003 - Lanteri, Luis (Estudios Económicos de El Colegio de México, 2005)
We estimate the total factor productivity for argentine agriculture over the period 1955 to 2003. One method of quantifying the impact of productivity is the use of growth accounting index numbers (Divisia index). However, some papers (see, for example, Hsieh, 2000) show that if technological change is not Hicks neutral then conventional total factor productivity index is not a satisfactory measure of this indicator, since that observed cost shares conflates the contribution of factor accumulation to output growth with that of technological change. In this paper, cost share equation system in the form of state-space model with latent variables are used to detect technological bias and to estimate the total factor productivity adjusted.